2022
DOI: 10.21203/rs.3.rs-1912529/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early stimulation and responsive care: a mediator of caregivers’ depression on the suspected developmental delay of left-behind children in China

Abstract: Purpose: Due to multiple factors, children left behind in rural areas suffer from delayed neurodevelopment (suspected developmental delay, SDD). This study aimed to analyze the effect of caregivers’ depression on left-behind children’s SDD, with early stimulation and responsive care mediating. Methods: A cross-sectional survey was conducted in villages of five Chinese counties. A total of 904 left-behind children and their primary family caregivers were enrolled. Information on the children and their caregiver… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In particular, previous studies showed that LBCs have a higher level of school dropouts ( Li and Hu, 2021 ; Wang Haining, 2021 ) due to the lack of parental supervision and family education ( Li and Hu, 2021 ), which heavily impacts LBCs in various aspects of their lives, such as their academic achievement ( Song et al, 2018 ; Wang et al, 2019 ; Gu, 2022 ), future life opportunities ( Ge et al, 2019 ), as well as they were suffered from mental health conditions ( Chen et al, 2022 ; Zhou et al, 2022 ), such as high suicidal thoughts ( Zhou et al, 2022 ), high risk of delayed neurodevelopment ( Li et al, 2021 ), depressive symptoms ( Ma et al, 2022 ), antisocial behavioural ( Liu et al, 2022 ), lower self-esteem ( Zhou et al, 2022 ) and lower self-efficacy ( Liang et al, 2018 ). He et al (2020) and Gao et al (2022) highlighted that improving the self-efficacy and academic performance of LBCs has become a widely discussed topic in academia recently.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, previous studies showed that LBCs have a higher level of school dropouts ( Li and Hu, 2021 ; Wang Haining, 2021 ) due to the lack of parental supervision and family education ( Li and Hu, 2021 ), which heavily impacts LBCs in various aspects of their lives, such as their academic achievement ( Song et al, 2018 ; Wang et al, 2019 ; Gu, 2022 ), future life opportunities ( Ge et al, 2019 ), as well as they were suffered from mental health conditions ( Chen et al, 2022 ; Zhou et al, 2022 ), such as high suicidal thoughts ( Zhou et al, 2022 ), high risk of delayed neurodevelopment ( Li et al, 2021 ), depressive symptoms ( Ma et al, 2022 ), antisocial behavioural ( Liu et al, 2022 ), lower self-esteem ( Zhou et al, 2022 ) and lower self-efficacy ( Liang et al, 2018 ). He et al (2020) and Gao et al (2022) highlighted that improving the self-efficacy and academic performance of LBCs has become a widely discussed topic in academia recently.…”
Section: Introductionmentioning
confidence: 99%